(untitled) (Teaching and Learning Inquiry, 2021)
Capstone experiences (CEs) serve a variety of purposes in higher education as opportunities to apply academic skills, explore post-graduate life and employment, and achieve a meaningful undergraduate event. This study investigated the purposes of CEs through a content analysis of institutional course syllabi/course outlines/module outlines and catalog/calendar descriptions at five institutions of higher education: a large public research university in Canada, a large public teaching university in the United Kingdom (UK), a college of a large public research university in the United States (US), and two medium-sized private liberal arts universities in the US. Using the CE purposes found in a review of scholarly literature as a research guide, the authors analyzed 84 institutional documents. CE purposes that appeared in the sample at lower percentages when compared with published studies included oral communication, a coherent academic experience, preparation for graduate school, preparation for life after college, and civic engagement/service learning. Implications for practice include the need for instructors and administrators to consider revising CE documents to better reflect the content and goals of the courses and to address the requirements of other audiences (e.g., program reviewers, accreditation evaluators). Moreover, the results of this study may assist educators in considering reasons for omitting explicit purposes from CE documents and/or justifying the inclusion of previously omitted purposes.